Occupational hazards and community-based safety practices among sanitation workers: Implications for social and environmental sustainability - Patrick Aaniamenga Bowan; Francis Jnr Tuuli Gamuo (Interaction, Community Engagement, and Social Environment, 2026)
Background: This study investigated occupational exposures experienced among sanitation workers in the Accra Metropolitan Area (AMA), Ghana. Despite performing essential functions that sustain urban hygiene and public health, sanitation workers often neglect their occupational health risks. This study explored the types and frequency of hazards faced by sanitation workers at AMA. Methods: Using a descriptive cross-sectional design, data were collected from 277 sanitation workers through a structured questionnaire. The analysis of the data involved both descriptive and inferential statistics. Findings: The study revealed that a majority of the sanitation workers were routinely exposed to hazards, including cuts, heat stress, dust inhalation, and contact with human waste. The study revealed that over 70% of the respondents had experienced work-related illnesses or injuries. Inferential analysis showed statistically significant relationships between consistent PPE usage and lower injury rates (p < 0.001), frequency of exposure and illness (p = 0.027), and experience level and health outcomes (p = 0.048). The study also exposed inequities in PPE access, especially among contract and casual workers. Conclusion: The study, therefore, recommends the establishment of inclusive safety policies aligned with national occupational health frameworks and the Sustainable Development Goals for sanitation workers in Ghana. Novelty/Originality of this article: The findings underscore the urgent need for systemic reforms in sanitation work policy in Ghana and other developing countries.